USULAN PERBAIKAN KUALITAS PADA TANGKI AIR MENGGUNAKAN METODE FMEA DAN FTA - Muhammad chabibi aziz; Deny Andesta (Universitas Putera Batam, 2022)
Along with the world's competition in the manufacturing industry, companies are required to increase productivity and quality in the resulting production. Companies engaged in construction and fabrication that produce water filter tanks located in Gresik Regency, in completing requests from customers always prioritize quality first and the company will try to win the competition by focusing on customer satisfaction. So far, the production process is not optimal because the number of defects is still too many. Product defects in the form of welding defects that occur during the production process, then painting defects that occur during finishing and symmetry defects in the machining process. To improve the production process, it is necessary to identify the type of failure, the consequences of the failure, and the cause of the problem to provide suggestions for improvement. To improve the production process in the water tank using the FMEA and FTA methods. Based on the FMEA method, the selected production process to identify based on the highest RPN, namely the welding process, painting process, and machining process that causes symmetry. This is done to minimize product defects and provide suggestions for improvement. After obtaining the RPN value from the FMEA method, then conducting an analysis using the FTA method to find the root cause of the problem that resulted in the production process being not optimal